Modern pharmacotherapy of chronic hepatitis C depending on the genotype of the hepatitis C virus - Kyreev, I; Zhabotynska, N (Annals of Mechnikov's Institute, 2019)
Hepatitis C is an infectious disease of the liver caused by the hepatitis C virus (HCV), which affects the liver and causes inflammation. This virus can cause both acute and chronic course of hepatitis in (70-80% of patients), which can vary according to the severity of the disease. The World Health Organization (WHO) estimates that about 71 million people worldwide suffer from chronic hepatitis C. According to estimates by national experts, Ukraine is among the countries with an average prevalence of hepatitis C. Every year, about 6,000 people are diagnosed with hepatitis C. There are 24,786 patients on the waiting list for treatment in Ukraine. Injecting drug users (IDUs) are most at risk of contracting HCV. The highest rate of HCV transmission is found in men who have sex with men. HCV can also be transmitted through tattoos, razors and acupuncture. Transmission of HCV from mother to fetus can be observed in about 4-5% of cases. Breastfeeding is safe. HCV is a spherical, enveloped, single-stranded RNA virus belonging to the Flaviviridae family. A genomic analysis of HCV led to the division of the hepatitis C virus into six genotypes. Subtype analysis was also righteous, which improved the genomic classification of HCV. HCV subtypes pose a serious problem for immune-mediated control of HCV and can explain the diverse clinical course of the disease and the difficulties in vaccine development. The article analyses the recommendations of the American Society of Infectious Diseases (IDSA) and the American Association for the Study of Liver Diseases (AASLD), in collaboration with the US International Antiviral Society (IAS-USA) on the pharmacotherapy of chronic viral hepatitis C. The pharmacotherapy of chronic HCV has two goals: 1. Achieving sustained HCV eradication or sustained virological response (SVR) – no serum HCV RNA 12 weeks after the completion of antiviral treatment. 2. Prevent the progression of cirrhosis, hepatocellular carcinoma, and decompensated liver disease requiring liver transplantation. To date, pharmacotherapy of chronic viral hepatitis C uses a combination of pegylated interferon (PEG-IFN) with ribavirin and direct-acting antiviral drugs (DAD). At the same time, very recently, priorities have been removed from the AASLD/ISDA recommendations and today treatment is strongly recommended for all patients with chronic viral hepatitis C. The addition of the oral nucleoside analogue of ribavirin to the PEG-IFN pharmacotherapy regimen marked a new era in the treatment of chronic HCV. The use of such a combination led to sustained eradication of HCV in 30-40% of cases. Pharmacotherapy with PEG-IFN alpha-2a and ribavirin can be individualized by genotype. Patients with HCV genotype 1 require treatment for 48 weeks and a standard dose of ribavirin. Patients with a genotype of 2 or 3 HCV genotypes adequately receive a low dose of ribavirin for 24 weeks. Relatively recently, a number of DADs were developed for specific effects on various replication sites of the hepatitis C virus. These include: protease inhibitors NS3 / 4A (boceprevir, voxilaprevir, telaprevir, simeprevir, grazoprevir, glecaprevir); NS5B protease inhibitors (sofosbuvir, dasabuvir); protease inhibitors NS5A (ledipasvir, daclatasvir, ombitasvir, elbasvir, velpatasvir, pibrentasvir). To date, according to the WHO recommendations, for the treatment of chronic viral hepatitis C, depending on the HCV genotype, in patients over 18 years old who have not received treatment, fixed combinations of DAD are used at the daily dosage. DAD for interrupting HCV replication in various places in different combinations showed 90-95% registered SVR compared to 50-70% in patients treated with PEG-IFN combined with ribavirin. However, clinicians should be aware that amino acid substitutions in the viral protein, associated with resistance to inhibitors and leading to drug resistance, can worsen the response to treatment of DAD, in particular, the base NS5A resistance in patients with chronic viral hepatitis C.